Utilizing Paraphrasing Tools, Translation Techniques, and Bilingualism to Enhance Argumentative Writing Skills - Suseno, Edy; Novitasari, Dian (Lia Center of Research and Education, 2025)
EFL students must improve their argumentative essay writing skills in order to cultivate critical thinking. Fifteen college students participated in the treatment because of their deficiencies in argumentative writing. The teacher began by delivering the lesson in the mother tongue. When it was put into practice, the students wrote argumentative essays in their home tongue. Strong external validation is required for the endorsed ideas. Citations were applied to the targeted notion in order to achieve this goal. The pupils had to manually translate their writings into English because of the subject matter. However, it is necessary to proofread the document for correct grammar usage. The pupils used a grammar checker app to meet this requirement. Making the content easy for readers to understand is crucial. The pupils used the paraphrase app in order to meet its requirements. The teaching-learning process data was then subjected to a qualitative analysis. The use of paraphrase tools, translation strategies, and bilingualism were then discovered to be beneficial for students' development of argumentative writing abilities. It encourages further observations from other researchers and could be used by educators to teach related subjects.